P232 Serum neutrophil gelatinase associated lipocalin (NGAL) as a marker of activity of Inflammatory Bowel Disease. (30th January 2023) - Ali, K; Bahgat, M; Borg, A; Maher, M; Abozeid, F
Abstract: Background: Inﬂammatory bowel disease (IBD) is a disease of activity and remission. Lipocalin 2 (LCN2), the coding gene for NGAL is one of the most over-expressed genes in the colonic mucosa in ulcerative colitis (UC) and crohn's disease (CD). In our research we investigated the utility of serum level of Lipocalin 2 in assessing the activity of IBD Methods: This was a single center case control study.It was conducted on 60 IBD patients, 50% (30 patients) were in remission and 50% were active.There were about 28 healthy control. Patients with IBD either UC or CD were enrolled from IBD clinic Mansoura specialized medical Hospital, Egypt. All patients and control group were subjected to investigations including complete blood count (CBC), Erythrocyte Sedimentation Rate (ESR), C-reactive protein (CRP), Fecal calprotectin and serum neutrophil gelatinase associated lipocalin (NGAL) by ELISA.Patients only were subjected to sigmoidoscopy or ileo-colonoscopy.The activity of IBD was assessed for UC by MAYO score and CD by CDAI. Results: NGAL showed significant increase among active IBD patients by mean± SD ng/ml (37.04 ± 9.63) than patients in remission (20.65± 4.35).It showed highly significant correlation with clinical and endoscopic activity of IBD r= 0.80, P<0.0001. Serum NGAL can easily discriminate patients with active IBD from healthy controls with AUC 95% C.I =1.00 (0.94-1.0), at the cutoff 18.52, P< 0.0001, with sensitivity 100% and specificity 100%. While AUC of NGAL which can discriminate patients with active IBD and those in remission at the cutoff 26.95 was 0.97, P< 0.0001, with sensitivity 93.3% and specificity 93.3%. In relation to fecal calprotectin, there was highly significant correlation between fecal calprotectin and serum NGAL (r=0.69, P< 0.0001).Both CRP and ESR were positively correlated to NGAL by r=0.38 and r=0.29 (P<0.05) respectively. Figure (1): NGAL ROC curve among active IBD cases versus healthy controls. Conclusion: Serum NGAL can easily discriminate patients with active IBD from healthy controls as well as among patients in active or remission of IBD. NGAL in comparison to other markers as fecal calprotectin or CRP or ESR shows better statistical performance for activity of IBD. This clarifies its ability to be a highly significant predictor of activity of IBD besides its lower cost.